Illite K‐Ar Dating of the Leibo Fault Zone, Southeastern Margin of the Tibetan Plateau: Implications for the Quasi‐Synchronous Far‐Field Tectonic Response to the India‐Asia Collision - Yuanhai Shu; Xuhua Shi; Samuel Haines; Hanlin Chen; Yong Zheng; Kongyang Zhu; Rong Yang; Haibing Li; Zhuona Bai; Jinhan Wang; Shufeng Yang (Geophysical Research Letters)
Abstract Whether tectonic strain from the early stage India‐Asia collision has synchronously affected the far‐field margin of the Tibetan Plateau is crucial for understanding plateau deformation and growth processes. However, direct evidence for early far‐field deformation remains scarce. Utilizing illite K‐Ar dating of three fault gouge samples, we established the faulting history of the Leibo fault zone (LFZ) at the southeastern margin of the Tibetan Plateau (SEMTP). Consistent authigenic illite ages of 52 ± 2, 54 ± 12 and 55 ± 6 Ma suggest the reactivated thrust faulting of the LFZ in the Early Cenozoic. Positioned ∼700 km east of the collisional boundary and at the intersection of three blocks with distinct lithospheric rheology in strength/viscosity, this event suggests a quasi‐synchronous far‐field tectonic response in the SEMTP to the India‐Asia collision.